Active Vibration Control of Composite Structures Using MicroBlaze™ Soft Core Processor on Virtex-4 FPGA - Prakash, Shashikala; Karthikeyan, C; Kumar, T G Renjith; Radhakrishna, P; Ravikiran, P G (Journal of Low Frequency Noise, Vibration and Active Control, 2014)
The present work investigates Multi – channel Active Vibration Control (AVC) of a composite research wing model and shell structure using modified Filtered × Least Mean Square (F×LMS) algorithm on Field Programmable Gate Arrays (FPGAs). AVC, using Digital Signal Processing (DSP) techniques are cost effective. But FPGAs, consuming small silicon area, have emerged as a dominant technology in embedded applications with potential features like high speed processing and low power consumption. Prominent features like high-speed parallel processing architecture along with hardware reconfigurability facilitates its usage to be wide spread in signal processing applications. An adaptive active vibration control system based on feed forward modified F×LMS algorithm implemented on FPGA hardware is presented here. The results from the Multi channel real time AV C studies are brought out in the paper.